2016
DOI: 10.3892/or.2016.4748
|View full text |Cite
|
Sign up to set email alerts
|

Improved antitumor activity and reduced myocardial toxicity of doxorubicin encapsulated in MPEG-PCL nanoparticles

Abstract: Abstract. Doxorubicin (Dox) is a broad-spectrum antitumor drug used for the treatment of many types of malignant tumors. Although it possesses powerful antitumor activity, its clinical application is seriously encumbered by its unselective distribution and systemic toxicities, particularly myocardial toxicity. Thus, it is imperative to modify Dox to decrease its systemic toxicities and improve its therapeutic index. In the present study, we adopted a novel type of monomethoxy poly(ethylene glycol)-poly(ε-capro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Despite its inhibitory effect on tumor growth, treatment with DOX significantly reduced mouse weight (Figure 6g). Histological analysis revealed that this side effect was caused by significant myocardial injury, a well‐known dose‐limiting factor for in vivo used of DOX;23 in contrast, DOX‐LANPs did not induce detectable myocardial toxicity nor damage to normal organs (Figure S7, Supporting Information). Kaplan–Meier survival analysis found that treatment with DOX‐LANPs significantly enhanced the survival of BCBMs‐bearing mice ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Despite its inhibitory effect on tumor growth, treatment with DOX significantly reduced mouse weight (Figure 6g). Histological analysis revealed that this side effect was caused by significant myocardial injury, a well‐known dose‐limiting factor for in vivo used of DOX;23 in contrast, DOX‐LANPs did not induce detectable myocardial toxicity nor damage to normal organs (Figure S7, Supporting Information). Kaplan–Meier survival analysis found that treatment with DOX‐LANPs significantly enhanced the survival of BCBMs‐bearing mice ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The effectivity of each drug has been reported at the clinical level in the treatment of several cancers besides CTVT (15)(16)(17)(18)(19)(20)(21)(22)(23). Until now, there were no reports of the use of 5-FU, methotrexate, gemcitabine, temozolomide, panobinostat, and toceranib in CTVT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…nanotechnological platforms have been recently assayed in zebrafish model to evaluate some of these parameters (Ang et al, 2017;Chen et al, 2017;Gao et al, 2017;Sun et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%